2021
DOI: 10.1371/journal.pone.0258576
|View full text |Cite|
|
Sign up to set email alerts
|

The magnitude of hypertension and associated factors among clients on highly active antiretroviral treatment in Southern Ethiopia, 2020: A hospital-based cross-sectional study

Abstract: Introduction Following the introduction of Highly Active Anti Retro Viral Treatment (HAART), the survival of people living with HIV/AIDS (PLHIV) has improved. However, hypertension remains a major challenge for people living with HIV. Very little effort has been made to examine the magnitude of hypertension and its contributing factors among clients receiving HAART, particularly in southern Ethiopia. Hence, the current study aimed at determining the frequency of Hypertension and associated factors among client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
0
12
3
Order By: Relevance
“…The prevalence of 17.5% in our population is comparable to those reported in Nigeria 29 , Zimbabwe 30 , South Africa 31 Zambia 32 and Tanzania 33 , but lower than those reported in Uganda 34 , Cameroon 35 , Brazil 36 , China 17 , 18 Ugandan rural study 37 and Argentina 38 . Similarly, our findings are higher than those reported in Ethiopia 16,39,40 and Kenya 41 . www.nature.com/scientificreports/…”
Section: Discussioncontrasting
confidence: 86%
“…The prevalence of 17.5% in our population is comparable to those reported in Nigeria 29 , Zimbabwe 30 , South Africa 31 Zambia 32 and Tanzania 33 , but lower than those reported in Uganda 34 , Cameroon 35 , Brazil 36 , China 17 , 18 Ugandan rural study 37 and Argentina 38 . Similarly, our findings are higher than those reported in Ethiopia 16,39,40 and Kenya 41 . www.nature.com/scientificreports/…”
Section: Discussioncontrasting
confidence: 86%
“…Others studies have reported an association of a longer duration ART with hypertension. 4 , 5 In another meta-analysis of HIV patients, it was revealed that longer duration of ART exposure was associated with an increased risk of hypertension. 31 The mechanism of how a longer duration on ART leads to hypertension is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension was 22.4% which is higher than the prevalence reported in Burundi, Tanzania, Uganda, among individuals living with HIV. 5,7,38,39 The prevalence was significantly highly prevalent in men than in females. Further, our results indicated that the prevalence of hypertension is higher among people aged more than 41 years.…”
Section: Discussionmentioning
confidence: 99%